Determination of relationships between leaf area Index and Stand characteristics in anatolian black pine stands of kastamonu region, Türkiye - Yer, Batin Mehmet; Sakici, Oytun Emre (FapUNIFESP (SciELO), 2022)
Background: Leaf area index (LAI) is an important stand characteristic in terms of forest productivity and stand growth, and it shows significant correlations with other stand characteristics. In this study, it is aimed to reveal the relationships between LAI and some other stand characteristics, i.e. mean diameter, stand age, dominant height, site index, number of trees, stand basal area, stand density, total crown biomass and crown dimensions for Anatolian black pine (Pinus nigra J.F. Arnold subsp. pallasiana (Lamb.) Holmboe) stands in Kastamonu region, which is one of the economically important tree species in Türkiye, and to develop a regression model for LAI estimations by using these relationships. Results: The data obtained from 119 temporary sample plots were used in the study. According to the results, stand basal area, stand density, total crown biomass, dominant height, number of trees, mean diameter, and site index positively correlated with LAI. LAI values were significantly different in terms of stand density and site classes. Among the candidate models for LAI estimations, the model containing site index and stand density as independent variables was the most successful model with the adjusted coefficient of determination (Radj2) of 0,63 and the Akaike information criterion (AIC) of-67,25. Conclusion: The LAI, which is difficult to measure directly in practice, of Anatolian black pine stands in Kastamonu region of Türkiye could be estimated accurately with the help of the equation developed. © 2022, Federal University of Lavras. All rights reserved.
Keywords: Pinus nigra; productivity; leaf area index; Stand density; stand dynamics; regression analysis; Kastamonu; Site index; LAI-2200C; Pinus nigra subsp. pallasiana; site index; 15. Life on land